Primary Science for the Caribbean: A Process Approach: Study-Workbook 7 for Standard 5 Common Entrance: Second Edition - Douglass, Raphael; Fraser-Abder, Pamela (Heinemann Educational Books, 1985)
To the teacher this study workbook is designed to help pupils achieve the aims and objectives set out in the SAPATT Common Entrance Guide. All SAPATT topics and processes are dealt with and there are additional activities to ensure adequate reinforcement. To pupils the study-workbook will help with primary school science. Pupils will observe, classify, measure, communicate, predict, infer, define operationally, formulate hypotheses, control variables, interpret data, and finally begin simple 'experimenting'.
Keywords: primary science; Common Entrance